Protecting All Children's Teeth (PACT): Oral Pathology - Melinda Clark; David Krol (MedEdPORTAL, 2013)
Abstract This resource reviews the differential diagnoses and management of oral pain, which is a common presenting complaint in the primary care office. It is imperative that pediatric healthcare professionals feel comfortable in the proper diagnosis, management, and triage of common oral pathology. This resource is a part of Protecting All Children's Teeth (PACT), a series created by the American Academy of Pediatrics' Oral Health Initiative to educate medical students, residents, pediatric primary care providers, and others interested in infant, child, and adolescent health about the importance of oral health in overall health. The series provides in-depth coverage of child oral health, oral health guidance, and preventive care to increase comfort in recognizing dental disease and conditions and communicating with dental professionals. This resource has been in use since 2007 by physicians in training at the medical school and residency levels, as well as those in clinical practice. The content has been used by pediatric, family medicine, and emergency medicine physician training programs, as well as by physician assistants, nurse practitioners, nurses, dentists, and dental hygienists in training and in clinical practice. As this presentation on oral injury is part of a complete oral health curriculum, educators and learners are encouraged to view the additional 12 courses.